Measuring Sustainable Livelihood in The Border Areas: The Case Study of Sangihe Island, North Sulawesi (Department of International Relations, Universitas Brawijaya, 2021)
This paper measures sustainable livelihood through the government poverty reduction program in Indonesia's border areas. We drew on primary field data sources and secondary data, including oral histories, in-depth interviews about livelihood, ecological, and documented evidence of environmental, socioeconomic, and institutional dynamics to identify the sustainability of poverty reduction programs. We use this information to understand whether the program is resilient or vulnerable. Cross-border areas are the most strategic position in building a country's image. One of the development priorities is to develop Indonesia from the periphery by strengthening regions and villages within the framework of a unitary state, especially the outermost villages and border villages. Sangihe Islands Regency is one of the border areas located in North Sulawesi Province. This paper is an initial analysis of the development of border areas and poverty alleviation programs in the Sangihe Islands Regency. The Sustainable Livelihood Approach is used to assess poverty reduction strategies in the Sangihe Islands Regency. The research shows that poverty in the Sangihe Islands Regency has become a main priority in the development program of the Sangihe Regional Government. National and Provincial governments support this program through the implementation of poverty alleviation. This program has had positive results, but it is vulnerable because it does not focus on sustainability.